2009
DOI: 10.1021/jp903726d
|View full text |Cite
|
Sign up to set email alerts
|

Diffusivity and Solubility of Organic Solutes in Supported Liquid Crystal Membranes

Abstract: The electro-optical properties of thermotropic liquid crystalline (LC) materials have been the subject of significant research effort due to their well-established applications in display technology; however, relatively little work has been done concerning the transport of dissolved solutes in LC phases, limiting their potential use in applications including chemical separation and sensing. Supported liquid crystal membranes were synthesized by impregnating porous cellulose nitrate (CN) membranes with 4-cyano-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 49 publications
0
13
0
Order By: Relevance
“…The cholesteric to isotropic transition, in which the light became extinct under crossed-polarization due to the lack of birefringence, was observed at 37 • C. Below the transition temperature, focal conic structures were observed, which indicate the presence of a cholesteric phase in the presence of untreated substrates (see supporting information). It has been reported that transition temperatures for LCs in confined geometries decrease slightly or remain unchanged [7,19]. The presence of a liquid crystal to isotropic phase transition at 37 • C was confirmed using polarized optical microscopy for the SLCM produced by embedding a 5CB-COC mixture embedded in a CN support (see supporting information).…”
Section: Liquid Crystal Phase Transitionsmentioning
confidence: 58%
See 2 more Smart Citations
“…The cholesteric to isotropic transition, in which the light became extinct under crossed-polarization due to the lack of birefringence, was observed at 37 • C. Below the transition temperature, focal conic structures were observed, which indicate the presence of a cholesteric phase in the presence of untreated substrates (see supporting information). It has been reported that transition temperatures for LCs in confined geometries decrease slightly or remain unchanged [7,19]. The presence of a liquid crystal to isotropic phase transition at 37 • C was confirmed using polarized optical microscopy for the SLCM produced by embedding a 5CB-COC mixture embedded in a CN support (see supporting information).…”
Section: Liquid Crystal Phase Transitionsmentioning
confidence: 58%
“…Chiral liquid crystalline (LC) phases were produced by doping achiral nematic LC materials (4-cyano-4 -pentylbiphenyl -5CB) with cholesterol based chiral dopants (cholesteryl oleyl carbonate -COC). Methods for the production of these membranes were previously developed by our laboratory for the preparation of achiral SLCMs [7]. This is the first use of cholesteric liquid crystals as the selective phase in enantiomer separation membranes, although a similar selective adsorption mechanism of enantiomers has been reported previously for chromatographic separations using cholesteric LC phases [8,9].…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…Disks (3.7 cm in diameter) were cut from the three-layered membranes and sandwiched between two pieces of aluminum tape (Han and Martin, 2009) having circular openings to expose an effective membrane area of 0.95 cm 2 . Silicone glue (RTV Silicone Gasket Maker, Ultra Copper, Permatex®) was used to seal the three-layered membrane where it contacts the aluminum tape, so that gas transport takes place only through the three-layered membrane itself.…”
Section: Three-layered Membrane Preparationmentioning
confidence: 99%
“…The slower heating rate was used to ensure equilibration of the fibers at each temperature up to the transition temperature. According to Fick's law (Han and Martin, 2009;Treybal, 1980), , the feed side outlet was closed so that the feed gas flows through the membrane under an applied pressure. Gas flow rate on the permeate side was measured using a flow meter (ProFLOW 6000, Restek) with an accuracy of 0.1 ml/min.…”
Section: Oxygen Permeation Experimentsmentioning
confidence: 99%